Design and development of carnival game - Ng, Hao Zheng (Nanyang Technological University, 2020)
In a carnival, games have to be light-weight and portable enough to be carried around easily. As carnivals are expected to last only a few days to a few weeks, it can be expected that games featured in these carnivals have to be easy to set up, as well as moved around for the convenience of the operator. In this project, a smaller, more portable version of the Stacker arcade game (henceforth referred to as “Mini-Stacker”) will be built. Besides the classic Stacker game, Mini-Stacker will also feature different game modes. An Arduino board will serve as the microcontroller and the external frame will be built using plywood. It will be built in the shape of a typical arcade machine to induce a sense of familiarity. A full-scale prototype of the Mini-Stacker is expected to be designed and built.